Pembingkaian ‘Feodalisme’ Kiai dan Santri di Pesantren oleh Media Xpose Trans7: Analisis Wacana Kritis Fairclough - Nissa Aurellia Putri; Nurhayati Nurhayati; Stevane Delsancy Pariama (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the forms of discourse produced by the television program Xpose on Trans7 in its coverage of pesantren. It examines how Xpose Trans7 frames the relationship between kiai and santri, and compares this framing with the concepts of ta’dzim and khidmah as practiced within the pesantren tradition. The analysis employs Norman Fairclough’s Critical Discourse Analysis framework. The findings indicate that the discourse produced is characterized by polarization and sensationalism. At the textual level, the program employs sarcastic narratives such as “wealthy kiai” versus “santri who give envelopes,” reinforced by negative analogies that reduce adab (ethical conduct) to the notion of punishment. Xpose Trans7 frames the kiai–santri relationship as exploitative and unjust. This framing stands in contrast to the traditional concepts of ta’dzim and khidmah, which are understood by santri as forms of spiritual devotion aimed at seeking blessing (barakah). The discourse reflects an underlying ideological divergence, wherein modern egalitarian values are mobilized to challenge the authority and traditional practices of pesantren.